2009
DOI: 10.1111/j.1600-0404.1984.tb00833.x
|View full text |Cite
|
Sign up to set email alerts
|

CT-detected hemorrhagic infarction; relation with the size of the infarct, and the presence of midline shift

Abstract: The incidence of mass effect indicated by midline shift, and the incidence of hemorrhagic infarction were studied in 952 consecutive CT scans with supratentorial infarcts. Hemorrhagic infarction was found in 5.1 % indicating that the incidence of hemorrhagic infarction during life is far less than was suggested from pathological studies. Midline shift was found in 3.6% and, accordingly, the chance of finding a hemorrhagic infarct with mass effect indicated by a shift of the midline would be 0.2% if these 2 phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In the present study of dogs, there was an equal number of ischaemic and hemorrhagic infarctions, which correlates with studies in humans, 21 but conflicts with a recent study of 40 dogs with brain infarction diagnosed by MRI in which all infarcts were classified non‐haemorrhagic 5 . Haemorrhagic lesions in our study were more likely to be associated with infarction having a mass effect, similar to findings in people 22 . It may be that MRI is more sensitive for detecting haemorrhagic infarcts not associated with a mass effect, causing this discrepancy, or the result may be attributable to the low number of cases in our study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the present study of dogs, there was an equal number of ischaemic and hemorrhagic infarctions, which correlates with studies in humans, 21 but conflicts with a recent study of 40 dogs with brain infarction diagnosed by MRI in which all infarcts were classified non‐haemorrhagic 5 . Haemorrhagic lesions in our study were more likely to be associated with infarction having a mass effect, similar to findings in people 22 . It may be that MRI is more sensitive for detecting haemorrhagic infarcts not associated with a mass effect, causing this discrepancy, or the result may be attributable to the low number of cases in our study.…”
Section: Discussionsupporting
confidence: 55%
“…5 Haemorrhagic lesions in our study were more likely to be associated with infarction having a mass effect, similar to findings in people. 22 It may be that MRI is more sensitive for detecting haemorrhagic infarcts not associated with a mass effect, causing this discrepancy, or the result may be attributable to the low number of cases in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Resolution capacity of CT scanner in 1984 was less sensitive [8] than that of more recent generation scanners. Moreover, studies using MRI to detect HT [6,7] reported a higher incidence of HT compared to those using CT [3,[8][9][10][11][12][13][14][15][16][17][18][19] . Risk of HT increases with the strength of treatment (antithrombotic, anticoagulant, thrombolytic) [1] and, as cardioembolic stroke is related to a greater risk of HT, studies including only cardioembolic stroke [10] might overestimate HT frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Furthermore, most of the information on the effect of early HT on clinical outcomes derives from studies on thrombolysis for ischemic stroke, [12][13][14][15][16] and data on early HT in patients not receiving thrombolysis mainly derives from patients randomized to placebo in the thrombolysis trials. 17,18 The aims of this prospective study in consecutive patients were therefore to assess: (1) the rate of early HT in patients admitted for ischemic stroke, (2) the correlation between early HT and functional outcome at 3 months, and (3) the risk factors for early HT.…”
mentioning
confidence: 99%